HEALTH AND RELIGION RELATIONS IN NEW MEDIA : THE COMMODIFICATION OF RELIGION IN HEALTH PROMOTION DURING THE PANDEMIC ON @PROMKES_KALTENG - Lestari, Mega Asri; Mualimin, Mualimin; Rosadhillah, Valencia Kirana (UIN Sumatera Utara Medan, 2023)
This study aims to analyze the commodification of religion in health promotion on the Instagram account @promkes_kalteng. Two aspects are the focus of the study in this research, namely the use of language and religious terms and the use of religious symbols. This study uses a qualitative method with a descriptive qualitative interactive media study approach. Data were obtained in two ways, namely observation and documentary studies. Specifically, the data obtained were analyzed using the Miles and Huberman model, namely data reduction, data verification, and conclusion. This study found two important points related to the commodification of religion in health promotion on the Instagram account @promkes_kalteng. First, three language or religious terms classifications are used in health promotion in the @promkes_kalteng account, related to the rituality, social, and health dimensions. The use of language or terms tends to legitimize the content of the message so that religious community groups can accept it. Second, the findings regarding using religious symbols in health promotion posts on the @promkes_kalteng account. The implications of these religious symbols are part of the tendency of the tool to transmit a message to strengthen the content of the message conveyed.